Urgent Needs to Consider and Assess the Transmission of Coronavirus (COVID-19) via Hospital Sewage and Wastewater - Laila Mandi (Journal of Clinical and Experimental Investigations, 2020)
The emergence and spread of SARS-CoV-2 responsible for COVID-19 disease are considered as a major threat to human health since WHO declared COVID-19 outbreak a global pandemic. In recent studies, scientists confirmed the presence of SARS-CoV-2 RNA in feces of COVID-19 patients and wastewater. In several areas, particularly low-income countries, hospital effluents are not disinfected or pretreated and they are mostly discharged into urban sewerage systems reaching wastewater treatment plants depending if it exists or not, consequently several infectious agents could be developed such as Coronavirus COVID-19 causing significant environmental and health risks. Several researchers across the world suggested that wastewater surveillance could be a sensitive tool to monitor the circulation of the virus in the population and may represent a complementary approach to measure the presence and the prevalence of current infectious disease when the capacity for clinical testing is limited. Only a few studies were done on the survival of Coronaviruses in wastewater and still there is limited information on its transmission potential through the environment. Taking into account the current situation, there is an urgent need to consider and assess the transmission of Coronavirus (COVID-19) via hospital sewage and wastewater. Further researches are imperative to fill the knowledge gaps in COVID-19 behavior in hospital and urban sewage, and wastewater treatment plants, identify the safety measures and better manage the pandemic phenomena.